Pengembangan Video Animasi Berbasis Canva pada Materi Makanan dan Sistem Pencernaan Makanan Kelas XI SMA/MA - Shinta Kurnia Dewi; Nurul Fauziah (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This preliminary study was conducted as the foundation for developing an animated video-based learning media using Canva. The main objective of this research is to present the initial data collected during the early investigation phase, which will serve as the basis for creating innovative, research-based learning media in the future. The development model applied in this research is the Plomp model, and the study has currently reached the preliminary investigation stage. Data were collected using several instruments, including interviews, classroom observations, and student needs assessment questionnaires. The results of the needs assessment revealed that the learning media currently used in schools is considered less effective, leading to difficulties for students in understanding the subject matter. Furthermore, 91.33% of students agreed that the development of an animated video-based learning media using Canva would be beneficial and support the learning process. These findings indicate a strong need for engaging, interactive, and technology-integrated learning media. The selected topic for development is “Food and the Digestive System,” which is part of the curriculum for grade XI students in senior high schools (SMA/MA), as this topic is often perceived as challenging. By utilizing Canva to create animated videos, it is expected that students’ learning motivation, conceptual understanding, and classroom engagement will significantly improve. The results of this preliminary study serve as an essential foundation for the next stages of development, ensuring that the final product will provide an effective and enjoyable learning experience tailored to students’ needs.